2022
DOI: 10.3390/nu14224844
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Concentration in Human Milk: A Meta-Analysis

Abstract: Humans require vitamin A (VA). However, pooled VA data in human milk is uncommon internationally and offers little support for dietary reference intake (DRIs) revision of infants under 6 months. As a result, we conducted a literature review and a meta-analysis to study VA concentration in breast milk throughout lactation across seven databases by August 2021. Observational or intervention studies involving nursing mothers between the ages of 18 and 45, with no recognized health concerns and who had full-term i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…The concentration of analytes in real samples, for instance, in food, biological uids (up to nmol), and pharmaceutical formulations (up to mg g −1 ), is low, and the molecular weight of analytes is small compared to coexisting foulants in matrices. 79,80 The presence of interfering species can adversely affect selectivity and sensitivity, and the capture of small-molecule analytes in complex food matrices and the signal transduction of sensing surface changes are challenging for sensors. 81 Many real samples contain complex matrices that can interfere with the electrochemical measurements of vitamins.…”
Section: Pretreatment Of Complex Vitamin Matrixesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of analytes in real samples, for instance, in food, biological uids (up to nmol), and pharmaceutical formulations (up to mg g −1 ), is low, and the molecular weight of analytes is small compared to coexisting foulants in matrices. 79,80 The presence of interfering species can adversely affect selectivity and sensitivity, and the capture of small-molecule analytes in complex food matrices and the signal transduction of sensing surface changes are challenging for sensors. 81 Many real samples contain complex matrices that can interfere with the electrochemical measurements of vitamins.…”
Section: Pretreatment Of Complex Vitamin Matrixesmentioning
confidence: 99%
“…The concentration of analytes in real samples, for instance, in food, biological fluids (up to nmol), and pharmaceutical formulations (up to mg g −1 ), is low, and the molecular weight of analytes is small compared to coexisting foulants in matrices. 79,80…”
Section: Challenges In Electrochemical Sensing Of Vitaminsmentioning
confidence: 99%
“…However, there are only a few review studies that have specifically investigated the longitudinal changes in minerals and vitamins in human milk. For instance, Dror et al focused on iodine and vitamin B-12 [ 13 , 14 ], Zhang H et al examined vitamin A [ 15 ], Xi Y et al reported on vitamin E [ 16 ], and Gidrewicz et al provided data on calcium and phosphorus from 1 to 12 postnatal weeks [ 17 ]. Another study by Yang et al surveyed nine minerals, but they only analyzed milk samples beyond 2 postnatal weeks: by then, the samples contain mature milk.…”
Section: Introductionmentioning
confidence: 99%
“…G-proteins are a family of signal transduction proteins playing a quite critical role in the transmission of extracellular signals into the cell [1]. They are involved in numerous physiological processes, including vision [2], olfaction [3], hormone secretion [4], and neurotransmitter release [5]. G-protein coupled receptors (GPCRs) is the largest kind of cell surface receptors and are responsible for Gprotein activation on ligand binding [6].…”
Section: Introductionmentioning
confidence: 99%